Digital payment adoption and managerial preferences in Madura’s culinary tourism sector: Evidence from the analytic hierarchy process - Nugroho, Ris Yuwono Yudo; Adiyanto, Mochammad Reza (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2025)
This study investigates the payment preferences of culinary tourism managers in Madura, with particular attention to the adoption of the Quick Response Code Indonesian Standard (QRIS) as a non-cash payment method. Employing the Analytic Hierarchy Process (AHP), the research identifies the key factors influencing payment decisions among managers across four districts in Madura. The results indicate that convenience is the most influential factor, followed by utility and safety. At the same time, QRIS remains the least preferred payment option compared to cash and other non-cash alternatives. Barriers to QRIS adoption include technical challenges, limited digital literacy, and insufficient infrastructure. The study underscores the need to strengthen technological infrastructure and enhance digital awareness to accelerate the adoption of non-cash payments within Madura’s culinary tourism sector. These findings contribute to the growing body of literature on financial inclusion and digital transformation in tourism, offering practical insights for policymakers and industry stakeholders seeking to promote inclusive digital economies.